Genetic variation for tuber mineral concentrations in accessions of the Commonwealth Potato Collection - Subramanian, Nithya; White, Phillip J.; Broadley, Martin R.; Ramsay, Gavin (Springer Verlag, 2017)
The variation in tuber mineral concentrations amongst accessions of wild tuber-bearing Solanum species in the Commonwealth Potato Collection (CPC) was evaluated under greenhouse conditions. Selected CPC accessions, representing the eco-geographical distribution of wild potatoes, were grown to maturity in peat-based compost under controlled conditions. Tubers from five plants of each accession were harvested, bulked and their mineral composition analysed. Among the germplasm investigated, there was a greater range in tuber concentrations of some elements of nutritional significance to both plants and animals, such as (Ca, Fe and Zn; 6.7, 3.6, and 4.5-fold respectively) than others, such as (K, P and S; all <3-fold). Significant positive correlations were found between mean altitude of the species' range and tuber P, K, Cu and Mg concentrations. The amount of diversity observed in the CPC collection indicates the existence of wide differences in tuber mineral accumulation among different potato accessions. This might be useful in breeding for nutritional improvement of potato tubers.